Pengaruh Pendidikan Kesehatan dengan Metode Demonstrasi Terhadap Kemampuan Merawat Kaki pada Penderita Diabetes Melitus Tipe 2 di Puskesmas Ranomuut Manado - Heldy Srikandhy Sadale; Silvia Dewi Mayasari Riu; Irma M Yahya (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2023)
Type 2 diabetes mellitus (DM) occurs when the body does not produce enough insulin to compensate for disturbed insulin production. Type 2 DM complications are diabetic ulcers. Feet care is an activity to carry out regularly to maintain hygiene in when the blood sugar levels increased or even in the normal condition. The objective of this research is to educate the health education to detect the peripheral neuropathy symptoms, minimize the risk of ulcers, amputations and prevent chronic complications.This is quasi experiment research with one group pre-post test design, using Mac-Nemar test taken 225 population of samples using Ari Kunto. 10% formula with Purposive sampling technique of 23 respondents.The researchers found there was a difference before and after given health education with the method of the ability to carry out for the feet demonstrated. Results Before performed the demonstration category both 2 people (8.7%) and category less good 21 people (91.3%), then the result After demonstration both 22 people (95.7%), and less good 1 person (4.3%) of 23 respondents, result P value = 0,000.Conclusion: The health education with demonstration methods on the ability to care for the feet of type 2 diabetics in Puskesmas Ranomuut Manado affected. Advice: Early research can add insight into the source of knowledge about how to prevent the occurrence of diabetic ulcers.